Peningkatan Pemahaman Operasional Siswa melalui KKN di SMK Al Islah Surabaya - Nuruddin, Mohamad Lutfi; Chusnaini, Azmil; Septia, Nurtiara; Amelia, Dyah Eka; Fitria, Nabilatul (Abimanyu : Jornal of Community Engagement, 2025)
The Community Service Program (KKN) is a form of university contribution in increasing the capacity of vocational education, especially in Vocational High Schools (SMK). This research aims to improve the understanding of SMK Al Islah Surabaya students on the concepts of production operational management and risk management. The method of implementing this activity is through structured and interactive material presentation, including material preparation, observation of student conditions, material delivery, open discussion, and evaluation based on student reflection using Google Form. The results of the activity showed an increase in student understanding both qualitatively and quantitatively. Before the activity, only 22% of students understood the production flow and 19% understood operational risks. After the activity, the understanding of the production flow increased to 80% and the understanding of risks to 76%. In addition, students showed awareness of the importance of work planning, division of tasks, and risk anticipation in production activities. This activity is in line with the principles of Work-Based Learning (WBL) and the Merdeka Curriculum, which emphasizes active, participatory learning, and is relevant to the needs of the world of work. Real experience-based material exposure has proven effective in improving the managerial readiness of vocational students.